Relações Lógicas estabelecidas por alunos de uma Quarta Série do Ensino Fundamental - Oliveira, Cecília Aparecida Virgílio de (2004)
This paper examines the production of numerical relations done by students of a 4th grade of elementary school at a public school in the city of Sao Paulo, S.P., Brazil. Several studies, in particular the ones done by Gimenez & Lins, Kamii and Franchi, show the need of establishing relations between the numbers, identifying meaning for the numbers and operations as a flexible way to solve problems. This flexibility can be searched through the interaction between arithmetic and geometric domains. Therefore, a series of activities were applied in order to search this flexibility. At first, these activities mobilized counting processes, notion of unity, quantitative relations interacted with geometry, particularly through the use of notions of perimeter and area as tools, according to the elements of didactics, tool-object and the interaction of domains developed by Douady. A confrontation was provoked between the notions of linear and bilinear magnitude through changes occurred on the sides of the rectangle, on its perimeter and area. These changes, according to Rogalski, have a deep relation with the addition and multiplicative structures. The use of the graph paper tries to favour not only the visual perception of the unity and the display of these unities in rectangular arrangement but also the comprehension of the area calculus and the multiplicative procedures. Both the records and the analysis of the data allowed concluding that the students initially set up quantitative relations such as the part-whole , single and multiple by establishing meaning for the numerical relations in the determination of numerical expressions. Thus, composition and decomposition of rectangular shape activities occurred in the relation part-whole , single and the multiple not only in the formation of new unities but also in the numerical relations. The findings of this study provided evidence that with the production of numerical relations, the students gave sense for the expressions, showed self-confidence and flexibility in the answers given